Auditory Brainstem Response in Neonatal Hyperbilirubinemia - Orfão, João (2022)
Objective: To establish the changes in auditory brainstem responses (ABR) associated to neonatal hyperbilirubinemia in term infants. Study design: Retrospective study. Material & Methods: The clinical records of 27 children born in Hospital Prof. Doutor Fernando Fonseca, who underwent ABR before 12 months of life, were reviewed. The ABR results were compared between the group of infants with hyperbilirubinemia (Group A) and the group without hyperbilirubinemia (Group B). Results: The interval I-V was longer in Group A (n=24 ears), compared to Group B (n=30 ears), p=0,46. There was no statistical difference in latency of peaks I, III or V, neither in intervals I-III or III-V (p>0,05) between groups, although they tend to be longer in group A. The limit of 20 mg/dl of total bilirubin was not related to significant differences in ABR parameters. Conclusions: Neonatal hyperbilirubinemia was associated to an increase in ABR measurements, which might traduce toxicity to the auditory pathway, even with bilirubin levels lower than 20 mg/dl.